Brand Dilution: An Analysis of The IKEA Versus IKEMA Dispute - Syahroni Syahroni; harits numan; Dini Dewi Heniarti (Universitas Pasundan, 2022)
This study is aimed to provide a different analysis related to dispute of trademark or brand of IKEA against Ikema. IKEA in the Judicial Review Verdict of Indonesia Supreme Court of (Peninjauan Kembali Mahkamah Agung), was asserted not having similarity with Ikema. On the other hand, the author views this case is potentially presumed as as a dilution case. Regarding this, the analysis employs theory that proposed by Shuy (2002) to uncover the identical similarity between the two trademarks. Graphemic and Phonetic analysis are used to establish the feature similarity, for analysis of public perception upon the both trademarks, psycholinguistic has been practiced. The result is the both trademarks are similar in terms of dilution. Keywords: dispute, dilution, linguistic analysis